Adolescent indoor tanning use and unhealthy weight control behaviors - Amrock, Stephen M; Weitzman, Michael (Journal of developmental and behavioral pediatrics, 2014)
Youth indoor tanning rates remain high despite the potential for increased melanoma risk. No previous study has assessed the prevalence of unhealthy weight control behaviors in both male and female adolescent indoor tanning users using a nationally representative survey. Pooled data on high school students from the 2009 and 2011 Youth Risk Behavior Survey were used (n = 26,951). Multivariate logistic regression was used to assess associations between the recent indoor tanning use and recently doing the following to lose weight: fasting for more than 24 hours; taking a pill, powder, or liquid without a doctor's consent; and vomiting or taking a laxative. Pooled data showed 23.3% of females reported indoor tanning within the past year; 6.5% of males did so as well. Adjusted multivariate results show that females who indoor tan were, on average, more likely to have fasted (odds ratio [OR], 1.2; 95% confidence interval [CI], 1.0-1.5), taken a pill, powder, or liquid (OR, 2.4; 95% CI, 1.9-3.0), and vomited or taken a laxative to lose weight (OR, 1.4; 95% CI, 1.1-1.7) within the past 30 days than those who did not. Males who indoor tanned within the past year were, on average, more likely to have fasted (OR, 2.3; 95% CI, 1.7-3.1), taken a pill, powder, or liquid (OR, 4.4; 95% CI, 3.3-6.0), and vomited or taken a laxative to lose weight (OR, 7.1; 95% CI, 4.4-11.4) within the past 30 days. Significant associations between indoor tanning use and unhealthy weight control behaviors exist for both male and female adolescents, with a stronger association observed among males.